Effect of a Primary Care-Based Chronic Disease Management Program for Hypertension Patients in South Korea - Eun-Whan Lee; Hee-Sun Kim; Bit-Na Yoo; Eun-Ji Lee; Jae-Hyun Park (Tehran University of Medical Sciences, 2022)
Background: Recently, the South Korean government has adopted a primary-care-based chronic disease management program as a national task. This study aimed to evaluate this program by focusing on hypertension patients and examine the effect of this program on their health. Methods: Overall, 863 subjects who responded to a survey and 1,716 subjects in administrative data were included. Effects of the program were evaluated based on intermediate outcomes (motivation for self-management, changes in health behavior, medical service utilization, duration of consultation with physicians, and medication compliance) and outcomes (disease management, service satisfaction, and physician-patient relationship, change of blood pressure). Furthermore, we compared study participants' baseline systolic and diastolic blood pressure with corresponding measurements obtained at examinations conducted at 3 and 6 months after baseline measurements. Results: Patients' motivation for self-management of hypertension, health behaviors (smoking, drinking, and exercise), regular clinic visit, and medication compliance were improved after participating in the program. Furthermore, patients' blood pressure levels were decreased while their satisfaction with physician-patient relationships was increased. Conclusion: Primary-care-based chronic disease management program is effective for managing hypertension. Therefore, it is essential to reinforce the role of community-based primary care to improve the health of patients with hypertension.